Upaya Meningkatkan Hasil Belajar Matematika Siswa Kelas IV SD Negeri 38/IX Jambi Kecil dengan Menggunakan Model Pembelajaran Kooperatif Tipe Two Stay Two Stray (TSTS) Tahun Ajaran 2018/2019 - Yusmanita Yusmanita (Jurnal Ilmiah Dikdaya, 2022)
This study aims to examine how to improve the mathematics learning outcomes of fourth grade students of SD Negeri 38/IX Jambi Kecil by using the two stay two stray (TSTS) type of cooperative learning model for the 2018/2019 academic year. This research uses Classroom Action Research (CAR). Respondents of this study were fourth grade students of SD Negeri 38/IX Jambi Kecil which consisted of 28 people. The results showed that the cooperative learning model type two stay two stray (TSTS) can improve the learning outcomes of fourth grade students at SD Negeri 38/IX Jambi Kecil. The increase can be seen from the average score of students on the pre-cycle test, namely (53.13) which is still in the "Less" category, while the score of students who reach the KKM is only 5 students or 17.86%; from the average score of students in the first cycle test, namely (57.42) which also falls into the "Less" category, while the score of students who reach the KKM is only 10 students or 35.71%; from the average score of students in the second cycle test, namely (63.92) which has entered the "Enough" category, while the score of students who have reached the KKM is 17 students or 60.71%; and the average score of students in the third cycle test is (66.78) which has also entered the "Enough" category, while the score of students who have reached the KKM is 22 students or 78.57%. It means that during the process of giving the action for three cycles, students experienced an increase of (13.65) points. The improvement that is more important is the changes that occur in the learning atmosphere of students in the classroom, especially regarding: attitudes, learning motivation, and student interactions in class. During the action process, the learning atmosphere becomes more active, students reduce undisciplined actions such as chatting in class, students appear more enthusiastic and happy to follow lessons, and in group activities they can participate more actively and contribute to problem solving in their groups, when as a host or as a guest.